Siyasah qadhaiyyah’s Invention on the Right to be a Victim of Revenge Porn - Frigia, Mada Dwita; Saebani, Beni Ahmad; Amin, Muhammad (Al Mashaadir : Jurnal Ilmu Syariah, 2024)
This research aims to investigate the background and rights of revenge porn victims in Bandung City, while also examining Siyasah Qadhaiyah's perspective on this issue. The research method employed is qualitative descriptive analysis with an empirical juridical approach to gather and analyze data related to these cases. The findings reveal that the background of revenge porn involves easy access to technology, extortion by former partners, and legal inadequacies in combating cybercrimes. LBH Bandung emphasizes the victims' need for legal, psychological, and social support. Victim rights, including privacy, control over personal information, access to justice, and legal protection, are crucial for their recovery and are regulated in various laws such as Human Rights Law, ITE Law, Pornography Law, and the Law on Elimination of Sexual Violence. Regarding Siyasah Qadhaiyah, there is alignment with the principles of state trust and responsibility in shaping regulations according to Islamic legal principles and public welfare. Government policies in formulating the Law on Elimination of Sexual Violence and efforts in psychology, technology, law enforcement, and preventive measures, signify an orientation toward the public interest. The impact of this research lies in a better understanding of the issue of revenge porn, highlighting the need for legal and psychological protection for victims, and ensuring the fulfillment of their rights for their recovery within society. It provides a foundation for further policies that accommodate victim protection and strengthen regulations related to cybercrimes.